2021
DOI: 10.1039/d1gc01914g
|View full text |Cite
|
Sign up to set email alerts
|

Constructing single Cu–N3 sites for CO2 electrochemical reduction over a wide potential range

Abstract: Cu-N-doped carbon nanotube with unsaturated coordination Cu atom (Cu-N3) was fabricated and exhibited over 90% CO faradaic efficiency (FE) in a wide potential range from -0.42 to -0.92 V. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The Cu‐N coordination of the DSAC PdN 4 /CuN 4 complex is lower than that of the original CuPc (CuN) complex. [ 20 ] The decrease in the CuN peak in PdN 4 /CuN 4 indicates that some Cu species may form copper oxide due to surface oxidation during air exposure. [ 21 ] , leading to the decrease in Cu in the macrocyclic structure host phthalocyanine (Pc 2– ).…”
Section: Resultsmentioning
confidence: 99%
“…The Cu‐N coordination of the DSAC PdN 4 /CuN 4 complex is lower than that of the original CuPc (CuN) complex. [ 20 ] The decrease in the CuN peak in PdN 4 /CuN 4 indicates that some Cu species may form copper oxide due to surface oxidation during air exposure. [ 21 ] , leading to the decrease in Cu in the macrocyclic structure host phthalocyanine (Pc 2– ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, among 11 Cu–N/C catalysts, CuN 3 V and CuN 2 V 2 with moderate adsorption strength of *COOH and *CO have better electrocatalytic CO 2 RR activity. In terms of the experiments, Feng et al 49 reported an unsaturated-coordinated Cu–N 3 catalyst with much higher catalytic performance than the saturated-coordinated Cu–N 4 catalyst. Zheng et al 48 reported an efficient CO 2 RR electrocatalyst with unsaturated-coordinated Cu–N 2 with better catalytic performance than the saturated-coordinated Cu–N 4 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The active center of monatomic copper catalysts is the Cu atom. 48,49,66 The structures under each type of adsorption mode were calculated, and the structures of the CO 2 RR species on the Cu-N/C catalyst surface are shown in Fig. 4 and S3, † while the adsorption energies are shown in Table 1.…”
Section: Adsorption Of Reaction Species On Cu-n/cmentioning
confidence: 99%
See 2 more Smart Citations